(untitled) (Physical Education, Health and Social Sciences, 2026)
Metronidazole benzoate is the drug that has been prescribed for bacterial disease conditions multiple times a day for longer period of time especially in patient suffering from bacterial disease, some of examples are acne vulgaris, rosacea and bacterial vaginosis. As in pharmaceuticals one of the focuses is to developed and formulate cheap and stable product with great therapeutic effect in order to have improved patient compliance. On data obtained from method development and validation, ICH guidelines were followed, the proposed UV method by using DMSO solvent s precise, reproducible and accurate. Hence this method is easy, feasible, cost effect for daily ongoing quality control testing of metronidazole benzoate by using DMSO as a soluble solvent.